2021
DOI: 10.1093/sleep/zsab206
|View full text |Cite
|
Sign up to set email alerts
|

Cortical thinning and sleep slow wave activity reductions mediate age-related improvements in cognition during mid-late adolescence

Abstract: Study Objectives Gains in cognitive test performance that occur during adolescence are associated with brain maturation. Cortical thinning and reduced sleep slow wave activity (SWA) are markers of such developmental changes. Here we investigate whether they mediate age-related improvements in cognition. Methods 109 adolescents aged 15-19y (49 males) underwent magnetic resonance imaging, polysomnography (PSG) and a battery of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 75 publications
1
2
0
Order By: Relevance
“…The first is the evolutionary development itself; that is, the maturation (emotional) processes that occur at these ages. This conclusion coincides with other previous studies [67,68]. The second is at the end of compulsory secondary education when students define their own curricular development (preferably in the fourth year).…”
Section: Discussionsupporting
confidence: 92%
“…The first is the evolutionary development itself; that is, the maturation (emotional) processes that occur at these ages. This conclusion coincides with other previous studies [67,68]. The second is at the end of compulsory secondary education when students define their own curricular development (preferably in the fourth year).…”
Section: Discussionsupporting
confidence: 92%
“…In recent examinations of the brain-sleep structure relationship across development, an association was found between the decrease in gray matter thickness and a decline in slow-wave electroencephalogram in adolescence [86,87]. Ong and colleagues [88] found that age-related improvement in processing speed among adolescents was associated with reduced gray matter thickness as well as reduced sleep slow wave activity and was not affected by sleepiness levels. The synaptic elimination model posits that in adolescence, as synaptic pruning proceeds, the intensity of brain activity declines, leading to increased sleepiness.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, while our current study does not test explanations of GM loss besides WM growth, evidence from other studies suggests a strong correspondence between GM shrinkage patterns and synaptic pruning patterns. For example, adolescent GM shrinkage is known to mediate a reduction in slow‐wave activity during sleep, which is a putative marker of synapse loss (Goldstone et al, 2018 ; Ong et al, 2021 ). Likewise, the GM shrinkage pattern is not only associated with expression profiles for genes related to myelin, but also with genes related to synaptic remodeling (Vidal‐Pineiro et al, 2020 ; Whitaker et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%